Analisis Elemen Maslahah Dan Mafsadah Dalam Pelaksanaan Aktiviti Kokurikulum Di Sekolah-sekolah Menengah Terpilih Di Negeri Kedah - Ahmad, Afnan Faiz Ridzuan (2022)
The national curriculum consists of learning and teaching sessions in classrooms as well as co-curricular activities. The implementation of co-curricular activities aims to strengthen learning in the classroom and provide a variety of interesting experiences to students. However, there are several issues in the implementation of co-curricular activities in schools, in which the implementation of the activities is not in line with sharia and contradicts with maqasid al-shari'ah that causes accidents to occur and endanger the lives of students. Therefore, this study has been conducted to investigate the concept of maslahah and mafsadah on the side of syarak, review the drafting development and implementation of co-curricular activities in schools as well as identify the elements of maslahah and mafsadah in the implementation of selected co-curricular activities in schools. The researcher has used both library and field studies in collecting data. This field study involved 8 secondary schools owned by the Ministry of Education Malaysia (KPM) located in the state of Kedah. The data collection which uses a semi-structured interview method has involved 17 respondents. The findings showed there has been an element of realising maslahah and avoiding mafsadah in the implementation of all co-curricular activities either under the uniformed bodies, sports games or club associations. The study also found that boarding schools have a longer time where co-curricular activities can be carried out in the evening. In addition, schools in the urban areas have better infrastructure facilities than schools located in rural areas.